2008
DOI: 10.1590/s0006-87052008000400019
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do alumínio sobre a absorção, o acúmulo e o fracionamento do fósforo em sorgo

Abstract: Efeito do alumínio sobre a absorção do fósforo em sorgo Bragantia RESUMOO trabalho teve como objetivo estudar o efeito do Al sobre a absorção, o acúmulo e o fracionamento do P em duas cultivares de sorgo. As plantas foram expostas a níveis tóxicos de Al durante dez dias e, então, colhidas e determinados o crescimento em tamanho e produção de massa seca, os teores de Al e de P total e as diversas formas de P nas duas partes das plantas. Avaliou-se, também, o efeito do Al sobre a absorção de P pelas raízes de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…1 and 2). This reduction in root growth has been observed in several studies with other plant species (Pereira et al 2008;Liu et al 2012;Freitas et al 2017). Because of the inhibition in root growth, shoot growth is negatively affected and this leads to a reduction in dry weight.…”
Section: Discussionsupporting
confidence: 57%
“…1 and 2). This reduction in root growth has been observed in several studies with other plant species (Pereira et al 2008;Liu et al 2012;Freitas et al 2017). Because of the inhibition in root growth, shoot growth is negatively affected and this leads to a reduction in dry weight.…”
Section: Discussionsupporting
confidence: 57%
“…This is because most of the P in plant tissue is found in inorganic forms (Casali et al, 2011;Marschner, 2012) and the inorganic P in the tissue makes up the labile compartment. These results corroborate with those obtained by Fernandes et al (2000), Pereira et al (2008), Casali et al (2011), and Oliveira et al (2016), who noticed that most of the tissue P is found in the soluble inorganic form in well-nourished plants grown in soil with sufficient nutrient content.…”
Section: Distribution Of P Forms In Cover Crop Residuessupporting
confidence: 92%
“…Because Al toxicity affects the root growth, it also affects the nutrient uptake. These effects were also observed in sorghum plants in which Al modified the kinetic constants of root P uptake, thereby decreasing the uptake of P (Pereira et al 2008).…”
Section: Discussionmentioning
confidence: 73%